1991
DOI: 10.2190/hv5j-4eyn-gpp7-y3qg
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness Effects on Substance Abuse Risk Factors and Use Patterns

Abstract: In this study, seventy-four adolescents in either a school, community or hospital based drug intervention program received and eight to nine week structured fitness activity class as an integrated element of their respective prevention or treatment program. Prepost assessments indicated significant gains in the field fitness tests of one mile run, 1 minute situp, 1 minute pushup, percent fat and flexibility for the total sample. Based upon prepost change on the one mile run time (less than 1:00) subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 10 publications
0
48
1
4
Order By: Relevance
“…For instance, a 12-week training program targeting adolescents and focusing on learning values and life skills through exercise reported a significant decrease in several risk factors associated with substance abuse and a concomitant reduction in the percentage of individuals who use cigarettes, smokeless tobacco, and alcohol (Collingwood et al, 2000). Similarly, a drug intervention program targeting at-risk adolescents and including an 8-week structured exercise class reported a significant decrease in anxiety, depression, and substance use in those participants exhibiting an improvement in physical fitness (Collingwood et al, 1991). Studies examining the efficacy of physical fitness programs in inpatient treatment facilities have also reported that exercise decreases depression and anxiety risk factors that are associated with relapse (Frankel and Murphy, 1974;Palmer et al, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…For instance, a 12-week training program targeting adolescents and focusing on learning values and life skills through exercise reported a significant decrease in several risk factors associated with substance abuse and a concomitant reduction in the percentage of individuals who use cigarettes, smokeless tobacco, and alcohol (Collingwood et al, 2000). Similarly, a drug intervention program targeting at-risk adolescents and including an 8-week structured exercise class reported a significant decrease in anxiety, depression, and substance use in those participants exhibiting an improvement in physical fitness (Collingwood et al, 1991). Studies examining the efficacy of physical fitness programs in inpatient treatment facilities have also reported that exercise decreases depression and anxiety risk factors that are associated with relapse (Frankel and Murphy, 1974;Palmer et al, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…Os descritores usados foram: "drug abuse" OR "drug dependence" AND "physical activity" OR "exercise"; "alcohol abuse" OR "alcohol dependence" AND "physical activity" OR "exercise"; "substance abuse" OR "substance dependence" AND "physical activity" OR "exercise" e "tobacco" OR "nicotine abuse" OR "tobacco abuse" AND "physical activity" OR "exercise", que forneceu um total de 159 trabalhos. [18][19] Alguns autores sugerem que após o exercício físico, os dependentes de álcool tem uma sensação de satisfação, e maior vigor físico, que pode propiciar um efeito tranquilizante, e analgésico, sem o uso do álcool. 16,18,27 Os efeitos agudos, com uma curta sessão de exercício físico sobre a dependência de tabaco têm sido mais amplamente investigados.…”
Section: Métodosunclassified
“…[18][19] Alguns autores sugerem que após o exercício físico, os dependentes de álcool tem uma sensação de satisfação, e maior vigor físico, que pode propiciar um efeito tranquilizante, e analgésico, sem o uso do álcool. 16,18,27 Os efeitos agudos, com uma curta sessão de exercício físico sobre a dependência de tabaco têm sido mais amplamente investigados. Cinco estudos desta revisão mostraram que os participantes que realizaram sessões agudas de exercício experimentaram uma redução da vontade de fumar durante o período de abstinência temporária de nicotina.…”
Section: Métodosunclassified
See 2 more Smart Citations